Acute phase mediator interleukin-6 and depression, work-related stress among young people (25-44 years old) - V. V. Gafarov; E. A. Gromova; E. V. Kashtanova; I. V. Gagulin; Y. V. Polonskaya; A. V. Gafarova; Yu. I. Ragino (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To study the association of interleukin-6 (IL-6) levels with depression and stress at work among young people (25-44 years old) in Novosibirsk.Material and methods. A random representative sample of young people (25-44 years old) in Novosibirsk was surveyed (975 people of both sexes; response rate, 71%) in 2013-2016 on the basis of Research Institute of Internal and Preventive Medicine — branch of the Institute of Cytology and Genetics (FWNR-2024-0002). All respondents signed informed consent. The World Health Organization MONICA-Psychosocial (MOPSY) scale was used to assess depression. Work-related stress was determined using the Karasek’s scale included in the program protocol. Quantitative determination of IL-6 was carried out in the laboratory of clinical biochemical and hormonal studies of therapeutic diseases of the Research Institute of Internal and Preventive Medicine — branch of the Institute of Cytology and Genetics.Results. High level of depression among people of both sexes aged 25-44 years were 11,9% (among men — 8,5%, among women — 14,6%). The level of IL-6 was higher in individuals of both sexes with high level of depression — 1,33 [0,72;3,92] pg/ml than without depression — 1,16 [0,63;2,37] pg/ml) (p=0,002). In women with high level of depression, IL-6 value was higher (1,31 [0,72;3,86] pg/ml) than in those without depression (1 [0,53;2,03] pg/ml) or a moderate depression — 1,06 [0,58;2,14] pg/ml, (p=0,002). The level of IL-6 was higher among people of both sexes who had changed occupation within the last 12 months (1,4 [0,67;3,58] pg/ml) than among those who had no changes — 1,12 [0,63;2,04] pg/ml. Among participants who assessed their work responsibility as very high, the median levels of serum IL-6 were higher (1,7 [0,72;5,48] pg/ml), than among people with high work load (1,37 [0,58;5,18] pg/ml), as well as with a moderate (1,21 [0,63;2,5] pg/ml) and a slight (1,09 [0,63;1,98] pg/ml) work load.Conclusion. A significantly higher level of IL-6 was found in depression and workplace stress among young people (25-44 years old) compared to people without depression and not experiencing workplace stress.